PENGARUH KOMPENSASI, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Faisalsya Rosa Halim; Ari Pradhanawati; Reni Shinta Dewi (Universitas Diponegoro, 2014)
Employee performance is affected by several factors, among which is the appropriate compensation, high work discipline and motivation to work well. This research aims to know and explain the effect of compensation, work discipline and motivation of work on performance of employees part production PT Sai Apparel Industries. This research type is eksplanatory research. Using data collection techniques interviews, questionnaires and observation. The conclusion from this study is that there are influences between compensation, work discipline and motivation of work on performance of employees. Based on these conclusions, then companies need to pay attention to matters concerning the guarantee of the maintenance of health, level of attendance in work, level of compliance and the level of recognition of conformity of work with a defined procedure. So it is expected to improve the performance of employees.